2009
DOI: 10.2337/db07-1056
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reactive Oxygen Species Are Obligatory Signals for Glucose-Induced Insulin Secretion

Abstract: OBJECTIVE-Insulin secretion involves complex events in which the mitochondria play a pivotal role in the generation of signals that couple glucose detection to insulin secretion. Studies on the mitochondrial generation of reactive oxygen species (ROS) generally focus on chronic nutrient exposure. Here, we investigate whether transient mitochondrial ROS production linked to glucose-induced increased respiration might act as a signal for monitoring insulin secretion.RESEARCH DESIGN AND METHODS-ROS production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
268
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(280 citation statements)
references
References 33 publications
6
268
1
5
Order By: Relevance
“…Mitochondrial redox signaling has therefore been proposed to be crucial for the regulation of energy metabolism (41,68). Furthermore, mitochondrial activation and redox changes are linked to the production of ROS at concentrations that impact signaling functions, as shown for glucose-induced insulin secretion (69). Our results establish a direct link between NCLX-mediated mitochondrial Ca 2ϩ extrusion and matrix redox state.…”
Section: Discussionsupporting
confidence: 56%
“…Mitochondrial redox signaling has therefore been proposed to be crucial for the regulation of energy metabolism (41,68). Furthermore, mitochondrial activation and redox changes are linked to the production of ROS at concentrations that impact signaling functions, as shown for glucose-induced insulin secretion (69). Our results establish a direct link between NCLX-mediated mitochondrial Ca 2ϩ extrusion and matrix redox state.…”
Section: Discussionsupporting
confidence: 56%
“…Results from the laboratories of the authors of this review have demonstrated that glucose induces an acute increase of Cu/Zn SOD activity, which increases H 2 O 2 generation in pancreatic islets (D. Morgan, E. Rebelato and A. Carpinelli, unpublished data), and that SOD activity is closely correlated with the rate of insulin secretion (r=0.96) [44]. While we have made a strong case for the involvement of H 2 O 2 in the promotion of insulin secretion, this is not a fully established fact with respect to all species studied, but does appear to be the case for mouse, rat and human beta cells [40,41,45] (D. Morgan, E. Rebelato and A. Carpinelli, unpublished data).…”
Section: Nadph Oxidase Isoforms and Components In Pancreatic Isletsmentioning
confidence: 89%
“…The classical ATP elevation-induced insulin closure of K ϩ channels may not be the only player for triggering insulin secretion (14,29). Evidence that ROS might contribute to glucose-stimulated insulin secretion is emerging (25,42). Leloup et al (25) strongly suggested that ROS are stimulators of insulin secretion independently of other products linked to glucose metabolism such as ATP.…”
Section: Discussionmentioning
confidence: 99%